The Influence of Work Discipline, Work Quality, Work Motivation, Leadership Style and Employee Satisfaction on Employee Performance at Shipyard Companies in Batam City - Yuswardi, Yuswardi; Asri, Dhita Hafizha; Valentino, James (REVITALISASI : Jurnal Ilmu Manajemen, 2024)
Human resource management (HRM) is a part of management that focuses on paying attention to potential or assets in the form of human resources which function as the main capital in internal improvement of organizations and companies. The company experienced a decline in employee performance due to low employee work discipline, especially in the operational department. The shipping industry in Indonesia is mostly located in Batam, where almost 60% of the 160 shipyards in Indonesia are in Batam. In recent years, the shipbuilding industry in Batam has developed quite rapidly. From the phenomena and background of the problem above, so that the resulting employee performance can be more optimal, it is thought to be influenced by the factor that has the most dominant influence, namely work discipline. This research is quantitative, using primary data. The data sources in this research were obtained from questionnaires on 400 respondents and literature studies. The research results show several things, namely work discipline influences employee performance, work motivation influences employee performance, work quality does not influence employee performance, leadership style influences employee performance, and job satisfaction does not influence employee performance. Keywords: Discipline, motivation, quality, leadership, satisfaction.